1ST INTERNATIONAL BASIC ONCOLOGY CONGRESS (Sabiad)
• THE THEME WITH “NEW HORIZONS IN CANCER RESEARCH: BIG DATA, SYSTEM BIOLOGY, NEW MOLECULAR DISCOVERIES” 02-04 JUNE 2022 • THE COURSE TITLED 'OMICS TECHNOLOGIES AND BIOLOGICAL INTERPRETATION IN CANCER RESEARCH' 04 JUNE 2022